Water extract from processed Polygonum multiflorum modulate gut microbiota and glucose metabolism on insulin resistant rats - Wen Gu; Min Yang; Qian Bi; Lin-Xi Zeng; Xi Wang; Jin-Cai Dong; Feng-Jiao Li; Xing-Xin Yang; Jing-Ping Li; Jie Yu (BMC, 2020)
Abstract Background The incidence of insulin resistance (IR) has rapidly increased worldwide over the last 20 years, no perfect solution has yet been identified. Finding new therapeutic drugs will help improve this situation. As a traditional Chinese medicine, PPM (processed Polygonum multiflorum) has widely been used in the clinic. Recently, other clinical functions of PPM have been widely analyzed. Results Administration of the water extract from PPM decreased the level of FBG, TC, and TG, and increased the level of FGC, thereby reducing the IR index and improving IR. Furthermore, Western blot analysis revealed that PPM significantly increased GPR43 and AMPK expression when compared with the MOD group, and GPR43, AMPK were known as glucose metabolism-related proteins. In addition, treatment with PPM can restore the balance of gut microbiota by adjusting the relative abundance of bacteria both at the phylum and genus level, and these changes have been reported to be related to IR. Methods Sprague Dawley (SD) rats were fed a high-fat diet and were gavaged daily with either normal saline solution or PPM for 12 weeks. Major biochemical indexes, such as fasting blood glucose (FBG), fasting glucagon (FGC), total cholesterol (TC), and triglyceride (TG) were measured. Then the protein expression of adenosine 5'-monophosphate -activated protein kinase (AMPK) and G protein-coupled receptor 43 (GPR43) was evaluated by using Western blot analysis. Moreover, the composition of gut microbiota was assessed by analyzing 16S rRNA sequences. Conclusions Our findings showed that PPM reversed the increasing of FBG and the decreasing of IRI, PPM accelerated the expression of glucose metabolism-related proteins and regulated the intestinal microecological balance. Therefore, we hold the opinion that PPM may be an effective option for treating IR.